Water quality of selected watercourses in Zasavje - Štaut, Lenart (Geografski vestnik, 2024)
Good surface water quality is one of the most important goals of sustainable water management, along with sufficient quantity. This paper presents an analysis of water quality in the Medija, Trboveljščica and Boben watercourses in Zasavje (central Slovenia), which are not included in regular water quality monitoring. Water quality was assessed on the basis of own field and laboratory analysis of selected physico-chemical parameters. In the period 2020-2021, 9 cyclical samplings were carried out at 16 locations at different times of the year. It was found that the rivers Trboveljščica and Boben are significantly polluted, while the river Medija is in a much better condition. In the headwaters, water pollution is relatively low and mainly due to agricultural activities, which is also reflected in better water quality. In the lower reaches, the Boben and Trboveljščica rivers in particular are subject to significant pollution from industry and households, which are also the main sources of pollution.
Keywords: Boben; environmental protection; fizikalno-kemijski parametri vode; hidrogeografija; hydrogeography; kakovost površinskih tekočih voda; Medija; onesnaženost vodotokov; physico-chemical water parameters; Slovenia; Slovenija; Trboveljščica; varstvo okolja; water quality; watercourse pollution; Zasavje